KOMIK PANCASILA (KOPALA) : MEDIA PENDAMPINGAN PENANAMAN NILAI PANCASILA PADA GENERASI PENERUS BANGSA - Fikriyah, Anis; Safitri, Ririn Indah (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2014)
Indonesia, a country which is famous with its eastern culture and manners currently had been hit by a moral crisis. However, moral is a main indicator to be considered and be built to achieve a good human resources quality so that we can build our nation. Besides, an intelligence with no moral will cause failure to achieve to build nationâs prosperity. The implementation of Pancasila by young generation nowadays tends to fade. Even the adults who had learned about P4 (penataran penghayatan dan penghayatan nilai- nilai Pancasila) got involved in various criminal cases, especially corruption. From this case, we can conclude that is there are many failures of implementation of Pancasila. The goal of this program is to re-embed the points of Pancasila to the next generation. This goal is such a real action to build the moral of the next generation who will lead Indonesia in a future. We used Pancasila Serial Comic as a method to apply the points of Pancasila.Keywords : Moral crisis, Moral, Pancasila, P4